ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL FISIKA TENTANG MATERI GERAK LURUS DI SMK 2 PONTIANAK - Suno, Jumito; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbtrakThis study aim to analysis about students error the solved line motion question physic at SMK Negeri 02 Pontianak. The from of this research was a suruey methed. The participant of this research consist of 32 students thet selected with purposive sampling technigue. In this research, the researcher were used essay test which consested of 5 guestion to measure students errors in filling out the guestion. Obtained of students errors in filling out the guestion in material rectilinear motion was 75,782% and the percentege of studentsÂ  ruis under standing was 85,417%. To find out the relationship both were used the product moment corelation. The result showed that found a negatiut relationship means that it the variable (x = 5,705406) hasincreased then the variable (y = 2,042) has decreased with a correlation coefficient -0,87 strong/hias category. The relationship between the two was significart that is t count > t table tabel = 5,705406 > 2,042, with a significant level 5% and dk = 30. The result of this research was the teacher expected to pay attentron to the students skills, so that can improved in the learning procest.Keywords : Students Errors In Filling Out The Guestion, Rectilinear Motion.